2022
DOI: 10.3390/ijerph191710935
|View full text |Cite
|
Sign up to set email alerts
|

Work from Home during the COVID-19 Pandemic—The Impact on Employees’ Self-Assessed Job Performance

Abstract: This study investigates the impact of remote workplace factors on employees’ social and technical self-assessed performance during the COVID-19 pandemic. The impact of the variables belonging to the employee’s profile, organizational environment, and work-life balance categories on social and technical performance were analyzed, based on a survey of 801 Romanian employees, using ordinary least squares and quantile regression techniques. While the first method provided summary point estimates that calculated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…During the COVID-19 pandemic, increased working from home, time spent alone, prevalence of unemployment, social isolation, and a lack of social contact due to social distancing may lead to loneliness and feeling stressful. [8][9][10][11] This plausible mechanism may support our main findings that the prevalence of smokers who were unemployed, and obese increased during the pandemic. In addition, along with growing evidence that e-cigarettes are no longer harmless alternatives to traditional cigarette, [12] preference for e-cigarettes has declined.…”
Section: Plausible Mechanismsupporting
confidence: 83%
“…During the COVID-19 pandemic, increased working from home, time spent alone, prevalence of unemployment, social isolation, and a lack of social contact due to social distancing may lead to loneliness and feeling stressful. [8][9][10][11] This plausible mechanism may support our main findings that the prevalence of smokers who were unemployed, and obese increased during the pandemic. In addition, along with growing evidence that e-cigarettes are no longer harmless alternatives to traditional cigarette, [12] preference for e-cigarettes has declined.…”
Section: Plausible Mechanismsupporting
confidence: 83%
“…Work–family conflicts leave miners prone to psychological problems and may lead to coal-mine accidents [ 15 ]. During the COVID-19 pandemic, employees forced into isolation were prone to job worries and mental disorders, creating work–family conflicts and, ultimately, affecting employees’ organizational performance [ 67 ].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Our work indicated better perceived performance of workers who had tutoring, without checking the age or degree of dependence on the tutor. Such absence of information may explain the difference to the findings of Kifor et al (2022) who indicated that having young children in the house (6 years or younger) has a negative impact on technical performance, on the other hand, there was convergence on the benefits of an adequate infrastructure for performing remote work (internet and dedicated workspace). The study of Kifor et al (2022) also found that employees who work from home are more likely to adapt to the new working environment and develop routines and strategies that allow them to work productively, compared to those employees who only occasionally turn their homes into offices.…”
Section: Consolidating the Analysismentioning
confidence: 83%
“…As this is a recent experience, there is great opportunity in the specialized literature to reflect on the 'permanent' consequences of the emergency adoption of remote work. Some first works (Kifor et al, 2022;Nolan et al, 2021;Pillai & Prasad, 2022) indicate that, after the pandemic, the system can continue as a mode of work, taking into account the nature of the work to be done and the personal conditions of the participants. There is a tendency for the work mode to remain, even if in combination with face-to-face or hybrid work.…”
Section: Consolidating the Analysismentioning
confidence: 99%